Interpretasi Mekanisme Erupsi Gunung Api Lokon berdasarkan Aktivitas Kegempaan Pra-Erupsi 4 – 12 September 2014 - Celvin Kristian Karisoh; Rolles Nixon Palilingan; Jeferson Polii (Jurnal FisTa : Fisika dan Terapannya, 2024)
Prior to the eruption of Lokon Volcano on September 13 2014 at 03.09 WITA, there were 62 volcanic earthquake events recorded by seismometers since September 4 2014. This research aims to interpret the eruption mechanism of Lokon Volcano based on seismic activity in the pre-eruption period. 04 - 12 September 2014. The distribution of source points for volcanic earthquakes, both hypocenters, can be visualized using the seismic method, namely by processing digital seimogram data using Swarm 3.1.0 software, GAD (Geiger's method with Adaptive Damping) and Origin 8. Data used, sourced from three stations, namely, Empung (EMP), Wailan (WLN), Kinilow (KIN). Lokon volcano. The hypocenter distribution of volcanic earthquakes is concentrated at a depth of 0 - 1,500 m above sea level and it was found that the aseismic area which is assumed to be a shallow magma pocket area from the Lokon volcano is at a depth of 1,500 - 3,000 m above sea level. The interpretation results show that the eruption mechanism of Lokon Volcano originates from disturbances in the volcanic system which are thought to be the result of tectonic earthquakes in the subduction zone. This causes the magma to rise upwards to supply shallow magma pockets until it reaches maximum pressure and an eruption occurs.